Macedonia and the Bible (Filološke studije, 2019)
The text precedes the influence of the Holly Book, the Bible, on the Macedonian culture and literature from the period of its origin to today. Due to the two types of testimony, the historical and the religious, it is an important source of information that has considerable significance for the vague history of Antique Macedonia. In the Medieval period, the Bible and the Christian philosophy have a dominant role in the set up of ideological and contemplative concepts; thus, the complete medieval literature had to be oriented towards contents and stylishly expressed methods taken from the Holly Book. The literature of enlightenment is, above all, educative, moral, and critical; that is to say, serving as mockery to the limited spiritual theological assertions. The Bible is a universal cultural fact with specific philosophy in which, apart from the traditional religious topics, the actual issues of the contemporary world may be involved. Universal thoughts included in it are used as grounds for many modern and postmodern works promoting the imagination of the new types of artists. Today, it is as if the Bible has lost its seriousness and significance as it is mirrored in the suppression of its classical role to intrude the code of consideration and behavior. Even though its function in “the multicultural, multi-meaningful society” is entirely distorted, it is stil fertile for setting up postmodern visions as a result of not only universality of foreseeing it comprises, but also its multilevel meaning: literal, symbolic, occult-esoteric, oracular etc., in favor of postmodern pluralistic ideas.